2007
DOI: 10.1196/annals.1423.055
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil in Lupus Glomerulonephritis

Abstract: Mycophenolate mofetil (MMF) is an immunosuppressive agent initially used in the treatment of transplant recipients. MMF has been used in renal, heart, and liver transplantation, where it seems more effective than other immunosuppressive regimens in reducing the incidence of acute rejection episodes. MMF has a variety of immunosuppressive effects, including selective suppression of T and B lymphocyte proliferation, and has been more recently used in many autoimmune inflammatory conditions. Systemic lupus erythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Indeed, it has been reported that deficient phagocytic activity and accumulation of apoptotic bodies could favor the progression of SLE (43). Because MPA mainly eliminated Ag-stimulated cells (not naive cells) through necrosis, we could conceive that the down-modulation of the immune activity associated with an identical or decreased amount of apoptotic bodies may account for the efficiency of MPA in treating SLE (44).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it has been reported that deficient phagocytic activity and accumulation of apoptotic bodies could favor the progression of SLE (43). Because MPA mainly eliminated Ag-stimulated cells (not naive cells) through necrosis, we could conceive that the down-modulation of the immune activity associated with an identical or decreased amount of apoptotic bodies may account for the efficiency of MPA in treating SLE (44).…”
Section: Discussionmentioning
confidence: 96%
“…Among 73 patients who received mycophenolate mofetil as therapy for ocular inflammation, corticosteroid-sparing success was achieved by 82% and 70% of patients ≤10 mg and the ≤5 mg prednisone thresholds respectively, the majority within 6 months, and 40% were able to discontinue prednisone completely 10. In an overlapping group of 129 patients on mycophenolate mofetil therapy, 70% achieved corticosteroid-sparing success after 6 months at the ≤10 mg prednisone level, and 12% were able to completely discontinue prednisone within 6 months 9. These reports were from one of the centers participating in the SITE Cohort Study; patients who started on mycophenolate mofetil during observation and were not on combination immunosuppressive therapy would be included in this report.…”
Section: Discussionmentioning
confidence: 98%
“…. Extraocular applications of mycophenolate mofetil therapy include prevention of renal allograft rejection, psoriasis, and various autoimmune diseases 9,10…”
mentioning
confidence: 99%
“…More recently, MMF has been introduced in the treatment of autoimmune rheumatic diseases, with encouraging results in adults. Its effectiveness has been proven in the induction and maintenance therapy of lupus glomerulonephritis through randomized controlled studies [5]. Few reports suggest a possible effective result in Systemic Lupus Erythematosus (SLE)-related hematological manifestations [6].…”
Section: Introductionmentioning
confidence: 99%